Desenvolvimento da agricultura de baixo carbono no Brasil - Tiago Santos Telles; José Eustáquio Ribeiro Vieira Filho; Ana Julia Righetto; Marina Ronchesel Ribeir (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– In 2009, Brazil has committed to reducing greenhouse gas (GHG) emissions. Since then, the National Policy on Climate Change has been instituted. In 2010, it was elaborated the Sector Plan for Mitigation and Adaptation to Climate Change for the consolidation of a Low-Carbon Economy in Agriculture (ABC Plan). The actions of the ABC Plan sought to recover degraded pastures, expand the adoption of integrated crop-livestock-forest systems, agroforestry systems, and the no-tillage system, spread biological nitrogen fixation, plant forests, and treat animal waste. In this context, this study aimed to verify changes in land use, the growth of Brazilian agricultural production and the fulfillment of the goals of the ABC Plan. From the results it is possible to verify that the international commitments agreed by Brazil were fulfilled. The expansion in the adoption of the ABC Plan technologies reached 154% of the target, and the equivalent CO2 mitigation 113% of the target. Howere, the recovery of degraded pastures and the treatment of animal waste are presented as the main barrier of the productive issue and for low carbon agriculture in Brazil. In terms of mitigation, it is necessary to increse investments in the recovery of degraded pastures and in the treatment of animal waste. In summary, the indicators demonstrate that Brazilian agriculture is increasingly focused on environmental sustainability and the development of low-carbon technologies, which are natural resources savers.
Keywords: Q01; Q50; Q56; 330; agriculture; livestock; natural resources; public policy; sustainability